2014
DOI: 10.1111/jog.12544
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vitamin C and vitamin E for prevention of postoperative adhesion: A rat uterine horn model study

Abstract: Administration of VC or VE i.p. was observed to be effective in the prevention of postoperative adhesion formation in an experimental model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
5
0
1
Order By: Relevance
“…In this study, erythrocyte and plasma MDA levels were found to be more important in the control group compared to heparin and sham group. It is observed that this result [7,9,10,12,40] is consistent with the notifications of the researchers. The increase in MDA in the control group is caused by cleavage of lipid-containing structures such as plasma and cell membranes of oxygen radicals by the cells involved in the inflammatory response during the adventitious process [28,43].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, erythrocyte and plasma MDA levels were found to be more important in the control group compared to heparin and sham group. It is observed that this result [7,9,10,12,40] is consistent with the notifications of the researchers. The increase in MDA in the control group is caused by cleavage of lipid-containing structures such as plasma and cell membranes of oxygen radicals by the cells involved in the inflammatory response during the adventitious process [28,43].…”
Section: Discussionsupporting
confidence: 90%
“…In another study, the difference in MDA level between the control group and sham groups was found to be significant [6]. In a study by Atilgan et al [10] MDA levels were found to be higher and more important in the adhesion group than in the control group. In a study carried out by Azine et al [12], it is found that the difference in tissue MDA levels between sham and control groups was statistically significant.…”
Section: Discussionmentioning
confidence: 84%
“…All of these features make it a good replacement for majority of drugs used postheart transplant care. Moreover, antiadhesion formation property and chemotherapy ability of Vitamin C adds credits to its therapeutic value as a prophylaxis against adhesion formation and malignant development postheart transplant 49–53 …”
Section: Discussionmentioning
confidence: 99%
“…These adhesions can be a serious cause of CVA development 20,48 . Vitamin C has been shown to reduce postoperative adhesions formation significantly in rats' models 49,50 . This makes Vitamin C one among the antiadhesive agents.…”
Section: Htr Cav and Ascorbic Acid (Asc)mentioning
confidence: 99%
“…Αντίθετα τα αποτελέσματα ήταν πιο ενθαρρυντικά και περισσότερο υποσχόμενα στην πρόληψη της ίνωσης μετά από ακτινοθεραπεία στην κοιλιακή χώρα ή την ελάσσονα πύελο, κυρίως όταν συνδυάσθηκε με πεντοξυφυλλίνη [202,208]. Όταν όμως στο παρελθόν η βιταμίνη Ε δοκιμάσθηκε για την πρόληψη των πειραματικών, μετεγχειρητικών, ενδοκοιλιακών συμφύσεων τα αποτελέσματα ήταν αμφιλεγόμενα [209,210]. Ωστόσο, παρά τα όσα αναφέρθηκαν παραπάνω και την έλλειψη σαφών αποδείξεων για τον προστατευτικό ρόλο που μπορεί να ασκούν οι βιταμίνες A, D, K και E μόνες τους ή σε συνδυασμό για την αποτροπή σχηματισμού ενδοκοιλιακών συμφύσεων, δε μπορεί να αποκλεισθεί το γεγονός ότι ίσως και να έχουν επηρεάσει θετικά, έστω και στο ελάχιστο, τα αποτελέσματα της παρούσας μελέτης.…”
Section: 'ελεγχος της κινητικότητας με διάφορες συγκεντρώσεις φωσφολιπιδίωνunclassified